A case study on the treatment of wastewater sludge from an electronic plant using cement - Irwan', T.; Agamuthu, P. Agamuthu (Malaysian Journal of Science, 2004)
Stabilization/Solidification (S/S) is a proven technology for the treatment of hazardous wastes. The process of manufacture and cleaning of electronic components can produce large quantities of waste, including hazardous waste, in the form of effluents, air emissions and solid waste. Direct disposal of these may cause environmental pollution, especially to surface and groundwater. Selection of stabilization/solidification as a remediation technology is also supported by recent developments in the environmental regulations. This paper focused on the laboratory studies of S/S disposal of wastewater sludge from an electronic plant, which generates about 150 tonnes of wastewater sludge per year. Three types of cement with or without activated carbon (AC) were used in this research, which include, Ordinary Portland Cement (OPC), Ground Granulate Blast furnace Slag (GGBS) and Mascrete Cement (MC). The American Nuclear Society (ANS) method indicated only Fe, Al, Cu but these were below the Standard B, EQA, 1974 while other metals were not detected. A comparison between Toxicity Characteristics Leaching Procedure (TCLP) and Japanese Leaching Test (JLT-13) methods indicated that JLT-13 gave lower leaching. The percentage of cement and activated carbon influenced TCLP and JLTÂ13 results.